Evaluation of optimal time blending process on medripal 412 And Prima XP SAE 20W – 50 samples with homogenity test - Ninin Asminah; Elli Prasetyo; Indah Dhamayanthie (Gema Wiralodra, 2023)
Prima XP SAE 20W - 50 is a multigrade lubricant used for gasoline and Medripal 412 engine lubricants used for marine industry engines which are non-carcinogenic and environmentally friendly. The main factor in testing lubricants is the Blending process, which is the process of mixing base oil with additives. In the blending process, an inhomogeneous lubricant was found which caused the lubricant test not to comply with specifications. This experiment aims to determine the optimal time of the blending process with the KAN homogeneity test method. Homogeneity testing can be seen from the viscosity value of the lubricant. So the optimum time for the blending process is needed for the continuity of the production process of this lubricant. Medripal 412 products have an optimum blending time of 30 minutes with a viscosity value at 100 C ranging from 14.79 mm2 / s based on the SNI 7069.1 Th. 2012, the product specification value of Medripal 412 is 12.5 - <16.3 mm2 / s and the Prima XP SAE 20W - 50 product has an optimum blending time of 45 minutes with a viscosity value at 100oC of 20.28 mm2 / s based on the SNI 7069.1 Th. 2012, the value of the Prima XP SAE 20W - 50 product specification is 5.6 - <21.9 mm2 / s. This shows that the lubricant is by the standard quality standards set by the company and the government so that the lubricant product is still suitable for use.